Effect of prolonged running-induced fatigue on free-torque components - Ryu, J.-S. (Korean Journal of Sport Biomechanics, 2016)
Purpose: The purpose of this study was to investigate the differences in FT (free-torque) components between non-fatigue and fatigue conditions induced by prolonged running. Methods: Fifteen healthy runners with no previous lower-extremity fractures (22.0 ± 2.1 years of age) participated in this study. Ground reaction force data were collected for the right-stance phase for 10 strides of 5 and 125-min running periods at 1,000 Hz using an instrumented force platform (instrumented dual-belt treadmills, Bertec, USA) while the subjects ran on it. The running speed was set according to the preferences of the subjects, which were determined before the experiment. FT variables were calculated from the components of the moment and force output from the force platform. A repeated- measures one-way ANOVA was used to test for significant differences between the two conditions. The alpha level for all the statistical tests was 0.05. Results: The absolute FT at the peak braking force was significantly greater after 5 mins of running than after 125 mins of running—which was regarded as a fatigued state— but there were no significant differences in the absolute peak FT or impulse between the conditions. Conclusion: The FT variables in the fatigue condition during prolonged running hardly affect the tibial stress syndrome.